Efforts to Prevent Drug Distribution and Smuggling in Rantauprapat Class IIA Prison by the Directorate General of Corrections for the North Sumatra Region - Asdah Armisa Tamba; Rahmat Efendy Al Amin Siregar; Riza Afrian Mustaqim (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
In Indonesia, the problem of drug trafficking and smuggling in correctional institutions (prisons), especially the Class IIA Rantauprapat Prison, is still a serious challenge. The high number of drug cases and the recurrence of smuggling modes indicate a weak surveillance system, prison conditions that exceed capacity, limited human resources, and the possibility of the involvement of officers. This is contrary to the main purpose of correctional services, which is the development and rehabilitation of inmates. This study aims to formulate strategies for preventing drug trafficking and smuggling in Class IIA Prison Rantauprapat and analyze the contribution of Islamic law principles in strengthening prevention policies. The research method used is qualitative with an empirical approach, through in-depth interviews with prison officers and data analysis from official documents, scientific articles, and laws and regulations. The results show that although multi-layered security systems and technologies such as X-rays have been implemented, major obstacles still occur, including high drug dependency of inmates, overcapacity that reaches 400% of normal capacity, weak internal supervision, and lack of spiritual guidance. The suggested strategies include strengthening security technology, increasing the integrity and capacity of officers, implementing rehabilitation programs based on religious values that are in line with sharia maqasid, as well as collaboration between institutions such as the Directorate General of Corrections, BNN, and the police. The synergy between positive law and Islamic law is believed to provide a strong foundation, both juridically and morally, to realize prisons as effective rehabilitation centers. This approach is expected to be able to break the chain of drug trafficking and foster inmates to become productive and noble individuals.